Subcutaneous injections of low doses of humanized anti-CD20 veltuzumab: a phase I study in chronic lymphocytic leukemia*. Issue 4 (2nd April 2016) - Kalaycio, Matt E.; George Negrea, O.; Allen, Steven L.; Rai, Kanti R.; Abbasi, Rashid M.; Horne, Heather; Wegener, William A.; Goldenberg, David M.
Abstract: To evaluate the potential of subcutaneous (SC) injections with anti-CD20 antibody veltuzumab in chronic lymphocytic leukemia (CLL), 21 patients received 80, 160, or 320 mg injections every 2 weeks × 4 doses ( n = 11) or 160 or 320 mg twice-weekly × 16 doses ( n = 10). Treatment was well tolerated with only occasional, mild-moderate, transient injection reactions. Lymphocytosis decreased in all patients (maximum decrease, 5–91%), with 12 patients obtaining >50% decreases. Of 14 patients with lymphadenopathy on CT imaging, 5 (36%) achieved 14–61% reductions (sum of perpendicular diameters). By NCI-WG criteria, two patients achieved partial responses (10%). SC veltuzumab appeared active in all dose groups, with no obvious exposure-response relationship, despite cumulative doses ranging from 320–5120 mg. Overall median progression-free survival was 7.7 months; three patients remained progression-free >1 year (2 ongoing at 2-year study completion). These data suggest further studies of SC veltuzumab in CLL are warranted.